Plant fiber reinforcements as alternatives in pultruded FRP composites manufacturing: a review - Balakrishnan, Thinesh Sharma; Hameed Sultan, Mohamed Thariq; Shahar, Farah Syazwani; Nayak, Suhas Yeshwant; Md Shah, Ain Umaira; Sebaey, Tamer Ali; Basri, Adi Azriff (Taylor and Francis, 2024)
Recent developments of green technology promote the rising attraction toward developing high-performance and environmentally friendly pultruded products from naturally derived resources. Some factors that attract attention to developing pultruded biocomposites are their lightweight properties, recyclability, and economical and environmentally superior alternatives to synthetic fibers in commercial applications. Researchers have studied that the environmental crisis caused by conventional synthetic materials can be reduced significantly by using sustainable materials instead. This paper aims to review the potential of plant fibers to be used in pultruded composite manufacturing to reduce and replace the use of synthetic materials in pultruded structures. It was found that kenaf and jute fibers have been extensively studied in pultruded plant fiber reinforced composites and pultruded glass/plant fiber reinforced hybrid composites for their mechanical and physical properties under various test parameters. Overall, pultruded PFCs have recorded good mechanical properties but have limitations in water absorption properties for outdoor applications. An overview of the optimum process parameters, limitations, and potential applications of pultruded PFCs are also outlined. Finally, this review summarizes the future scopes and expectations, providing researchers and industrialists with a vision for deeper investigation in developing pultruded PFCs.